Satire in the Middle Byzantine Period : The Golden Age of Laughter? - Marciniak, Przemysław (Explorations in Medieval Culture Ser, 2020)
Intro -- Contents -- Figures -- List of Contributors -- Note on Transliteration -- Chapter 1 It is Difficult Not to Write Satire: A Brief Introduction to the Satirical Mode -- Part 1 Traditions, Approaches, and Definitions -- Chapter 2 The Fortune of Lucian in Byzantium -- Chapter 3 Laughter, Derision, and Abuse in Byzantine Verse -- Chapter 4 Parody in Byzantine Literature -- Part 2 Forms and Functions -- Chapter 5 Satirical Elements in Hagiographical Narratives -- Chapter 6 Political Satire -- Chapter 7 Parody in Byzantine Art -- Chapter 8 The Cicada and the Dung Beetle -- Part 3 Satire as a Philological Endeavor -- Chapter 9 The Power of Old and New Logoi: The Philopatris Revisited -- Chapter 10 A Satire Like No Other: Pseudo-Lucian's Charidemos and Its Traditions -- Chapter 11 The Consolation of Philology: Anacharsis or Ananias -- Part 4 Komnenian Satire: A Golden Age? -- Chapter 12 Playwright, Satirist, Atticist: The Reception of Aristophanes in 12th-Century Byzantium -- Chapter 13 Satirical Modulations in 12th-Century Greek Literature -- Chapter 14 Satire in the Komnenian Period: Poetry, Satirical Strands, and Intellectual Antagonism -- Chapter 15 "For Old Men Too Can Play, Albeit More Wisely So": The Game of Discourses in the Ptochoprodromika -- Chapter 16 Afterword -- Appendix Nikephoros Basilakes on His Own Satirical Writings -- Bibliography -- Index.